1976
DOI: 10.1071/ch9761825
|View full text |Cite
|
Sign up to set email alerts
|

The influence of pressure on the infrared spectra of hydrogen-bonded solids. IV. Miscellaneous compounds

Abstract: Measurements have been made of the influence of pressure on the stretching and bending frequencies of hydrogen bonds in a further series of 15 solid compounds. Two exceptions have been found to the general rule that an increase of pressure decreases the X-H stretching frequencies of weak and medium-strength X-H. 3 .Y bonds. Possible explanations are offered of the exceptions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 0 publications
1
30
0
Order By: Relevance
“…For the ν(OH) mode in Figure 10(d), its linear blueshifts from ambient pressure to 10.3 GPa reflects that hydrogen bonds in SST are strong, and continue to be strengthened with increasing pressure. 48 However, the ν(OH) mode disappears at 10.3 GPa and cannot be detected in higher pressure region. This indicates that across the phase transition, water molecules in SST have changed into disordered states.…”
Section: Resultsmentioning
confidence: 97%
“…For the ν(OH) mode in Figure 10(d), its linear blueshifts from ambient pressure to 10.3 GPa reflects that hydrogen bonds in SST are strong, and continue to be strengthened with increasing pressure. 48 However, the ν(OH) mode disappears at 10.3 GPa and cannot be detected in higher pressure region. This indicates that across the phase transition, water molecules in SST have changed into disordered states.…”
Section: Resultsmentioning
confidence: 97%
“…Several high-pressure studies on Pentaerythritol, C (CH 2 OH) 4 , (PET) have been reported (FROLOV et al [1962], , HAMANN and LINTON [1976] and KATRUSIAK [1995]). FROLOV et al [1962]) have measured, by X-ray powder diffraction, the unit-cell dimensions as a function of pressure up to 883 MPa.…”
Section: Introductionmentioning
confidence: 99%
“…The discontinuities observed in the compression of the lattice constants a and c between 410 and 550 MPa have been interpreted as due to a first order phase transition in that pressure range. The pressure-induced phase transition seemed confirmed by the pressure dependence of the electrical conduction of PET by ZHORIN et al [1962] and its IR spectra by HAMANN and LINTON [1976]. KATRUSIAK [1995] has carried out high-pressure single-crystal X-ray diffraction studies on PET to obtain information regarding the pressure-induced phase transition of PET and to analyse the external and the internal strains of the crystal in relation to its structure.…”
Section: Introductionmentioning
confidence: 99%
“….H δ− distance. So, if there is any dihydrogen bonding in the material, the N-H stretching should exhibit redshift with pressure (25)(26)(27)30) with some exceptions that have very strong symmetric dihydrogen bonding (39)(40)(41)(42)(43)(44)(45)(46). As shown in Fig.…”
Section: −δmentioning
confidence: 99%